150k views
1 vote
Which expression is equivalent to -3x+24? Select two answers!

A. -3 (x - 8) (This one is correct ik)
B.- (3x + 24)
C. 3/2 (-2x + 16)
D.-1/3 (9x + 8)
E. 6 (-1/2x - 4)

1 Answer

0 votes

Answer:

The option A and C are correct that is


-3(x - 8)\\\ (3)/(2)(-2x +16)

Explanation:

Given:


-3x + 24 \\ \textrm {is quivalent to}\\-3(x - 8) = -3x --3*8 = -3x + 24\\\\(3)/(2)(-2x + 16) = (3)/(2)*-2x + (3)/(2)* 16 = -3x + 24

Therefore, The option A and C are correct that is


-3(x - 8)\\\ (3)/(2)(-2x +16)

User Mygod
by
5.5k points